1998
DOI: 10.1029/98gl00858
|View full text |Cite
|
Sign up to set email alerts
|

Soufrière Hills Eruption, Montserrat, 1995–1997: Volcanic earthquake locations and fault plane solutions

Abstract: Abstract. A total of 9242 seismic events, recorded since the start of the eruption on Montserrat in July 1995, have been uniformly relocated with station travel-time corrections. Early seismicity was generally diffuse under southern Montserrat, and mostly restricted to depths less than 7 kin. However, a NE-SW alignment of epicentres beneath the NE flank of the volcano emerged in one swarm of volcano-tectonic earthquakes (VTs), and later nests of VT hypocentres developed beneath the volcano and at a separated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(67 citation statements)
references
References 8 publications
6
61
0
Order By: Relevance
“…Phase equilibria and melt inclusions indicate that the magma at depth contained 4-5 wt.% H 2 O in the rhyolitic melt phase (Barclay et al 1998). Temperature and water pressure conditions are estimated at 830-860°C and about 120-140 MPa , consistent with the seismic estimate to top of magma reservoir at >5 km (Aspinall et al 1998).…”
Section: Erupted Magmassupporting
confidence: 63%
“…Phase equilibria and melt inclusions indicate that the magma at depth contained 4-5 wt.% H 2 O in the rhyolitic melt phase (Barclay et al 1998). Temperature and water pressure conditions are estimated at 830-860°C and about 120-140 MPa , consistent with the seismic estimate to top of magma reservoir at >5 km (Aspinall et al 1998).…”
Section: Erupted Magmassupporting
confidence: 63%
“…Fault intersections produce zones of enhanced permeability and also produce crustal weaknesses that can act as preferential magma pathways. The area beneath SGH has been the site of periodic seismic swarms that have been recorded in 1933-1937, 1966-1967, and 1992-1996; there was also a preinstrumental seismic crisis 1897-1898 [Aspinall et al, 1998] that was also associated with this area. These seismic crises are consistent with repeated magmatic injection episodes occurring beneath SGH as well as SHV.…”
Section: Discussionmentioning
confidence: 99%
“…[7] EQ swarms with hypocenters beneath SGH occurred between 1995 and 1997 [Aspinall et al, 1998] in the vicinity of the geothermal system. A study of all located EQs detected by the Montserrat Volcano Observatory network showed that virtually all local seismicity has been located beneath the SHV since 1997.…”
Section: Data and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing eruption began on 18 July 1995 Aspinall et al, 1998) following a three-year period of precursor seismic activity. The eruption has been characterized by the growth of an andesite lava dome with associated pyroclastic flows (PF), vulcanian explosions and debris flows.…”
Section: Eruption Chronologymentioning
confidence: 99%